Development and evaluation of tractor operated transplanter for wash root paddy (Oryza sativa) nursery - SINGH, NEERAJ KUMAR; NARANG, MAHESH KUMAR; PRAKASH, APOORV; THAKUR, SURINDER SINGH; SINGH, MANJEET; DIXIT, ANOOP KUMAR (The Indian Journal of Agricultural Sciences, 2025)
Most of the paddy (Oryza sativa L.) crop is typically transplanted manually by migrant workers in north-western Indian region. Despite several efforts to promote the existing mat-type nursery-fed paddy transplanter, farmers have not adopted this technology as well as NAREGA act of Government of India impedes the migrant workers movement to the region and creates labour crises during peak transplanting season. Therefore, there is a need of transplanter for wash root nursery. The study was carried out during rainy (kharif) season of 2020 and 2021 at Punjab Agricultural University, Ludhiana, Punjab to develop and evaluate paddy transplanter for wash root nursery under field conditions. Age of nursery was selected as independent parameters whereas the hill to hill spacing missing index, multiple index, field capacity, damage percentage, yield, fuel consumption and cost of operation were observed. The age of nursey has significant effect on missing index, multiple index, damage percentage, field capacity and cost of operation whereas, hill to hill spacing, planting efficiency, fuel consumption and yield has non-significant effect. Thirty-five days of nursery was found optimum for the developed paddy transplanter under field evaluation at fixed forward and mechanism speed. At this combination, the mean hill to hill spacing, missing index, multiple index, field capacity, damage percentage, planting efficiency, yield, fuel consumption and cost of operation were 142.5 mm, 31.18%, 4.40%, 0.29 ha/h, 4.44%, 60.75%, 4.75 t/ha, 4.13 L/h and 10,136.25 ₹/ha, respectively. The developed transplanter could results in increasing the mechanisation index in transplanting/sowing operation which is lowest as compared to other field crops.